Tensile behavior of alloy 718 in hot corrosive environment - Mahobia G.S.; Paulose N.; Mannan S.L.; Chattopadhyay K.; Santhi Srinivas N.C.; Singh V. (My University, 2025)
Nickel-iron-based alloy 718 was thermally exposed in peak-aged condition at 550 and 650 C, from 5 to 100 h, with and without salt coatings and was tested in tension at room temperature and elevated temperatures. Standard tensile specimens were coated with three different salts (in wt.%): NaCl(100), Na 2SO4 + NaCl (75/25), Na2SO4 + NaCl + V2O5 (90/5/5). Exposure of salt-coated specimens at 550 and 650 C revealed formation of scales and corrosion pits. Tensile deformation resulted in cracking of the surface oxide/corrosion scale. The uncoated specimens showed formation of oxide scales on the surface, without any cracking whereas the salt-coated specimens showed surface cracking and pitting at some places. However, tensile properties were not degraded due to salt coatings. © 2013 ASM International.